Multiproduct Mergers and the Product Mix in Domestic and Foreign Markets - Jackie M.L. Chan; Michael Irlacher; Michael Koch (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the effects of mergers on the product mix of multiproduct firms. Thus, we open the black box of post-merger efficiency improvements to reveal a new margin of adjustment along the product dimension. We analyze horizontal mergers in a theoretical model where oligopolistic firms employ a flexible manufacturing technology and allocate assets between differentiated varieties. After a merger, acquirers drop products from their consolidated domestic product portfolio and reallocate assets towards core varieties. We further demonstrate that such merger-induced efficiency gains imply greater activity in foreign markets. Using detailed Danish register data, we document novel facts regarding mergers and multiproduct firms and find empirical evidence strongly supporting the model's predictions. Our results show that the number of domestic products of the post-merger acquirer falls relative to the sum of the premerger acquirer and target, that skewness of domestic sales rises towards core products, and that export activity increases.
Keywords: F12; F14; G34; L22; L25; 330; multiproduct firms; horizontal mergers; flexible manufacturing; exports; product mix; event study